step 1
In the given smaller right triangle on the bottom
we have that
Applying the Pythagorean Theorem
![z^2=y^2+3^2\text{ ----> equation 1}](https://img.qammunity.org/2023/formulas/mathematics/college/dfn8l2w6oidmxadr7tc4femgms4sjgzbhc.png)
step 2
In the complete right triangle
we have that
Applying the Pythagorean Theorem
![\begin{gathered} (7+3)^2=x^2+z^2 \\ 10^2=x^2+z^2\text{ -----> equation 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l0qn6sr9qjk2uvy2kz4ux5802x350fbra8.png)
step 3
In the right triangle of the top
Applying the Pythagorean Theorem
![x^2=7^2+y^2\text{ -----> equation 3}](https://img.qammunity.org/2023/formulas/mathematics/college/cd1rujicc1hfgt0qinmj3hmkxx2v0ooesr.png)
step 4
Substitute equation 3 in equation 2
![\begin{gathered} 10^2=(7^2+y^2)+z^2 \\ 100=49+y^2+z^2\text{ -----> equation 4} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hypzizck7klm20f8bf676tbwgc0iiqom9f.png)
step 5
substitute equation 1 in equation 4
![\begin{gathered} 100=49+y^2+(y^2+9) \\ solve\text{ for y} \\ 2y^2=100-58 \\ 2y^2=42 \\ y^2=21 \\ y=√(21) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/23zbfsx4tfevsb8qh99v0st9pdigu6ihnh.png)